Combined experimental/numerical study on the precipitation of nanoparticles - Peukert, Wolfgang; et al. (Aiche Journal, 2004)
Nanoparticle precipitation in a T-mixer was investigated experimentally as well as through simulations based on the population balance equation coupled with a global mixing model using barium sulfate as the substance under investigation. A detailed predictive precipitation model is presented and the important model parameters are identified: the mixing kinetics, the interfacial energy, and the physicochemical calculation of supersaturation. Furthermore, the capability of the global mixing model was evaluated, achieving good agreement of the mean particle sizes between experimental and simulation results. Many insights into the kinetics and the relevant time scales of the competing steps such as micromixing (mixing at the molecular level), nucleation, growth, and aggregation are obtained. However, some discrepancies in the width of the particle size distributions remain that are attributed to spatial and temporal fluctuations in the flow field and, consequently, in the mixing kinetics that cannot be resolved by the applied global mixing model. © 2004 American Institute of Chemical Engineers.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.combin
Keywords: Barium sulfate; Interfacial energy; Micromixing; Nanoparticle; Population balance equation; Precipitation